A study of cloud-to-ground lightning flashes initiated by fast positive breakdown - Sabri M.H.M.; Ahmad M.R.; Al-Kahtani A.A.N.; Kadir M.Z.A.A.; Baharin S.A.S.; Lu G.; Zhang H.; Williams E.; Cooray V.; Nordin F.H. (Elsevier Ltd, 2023)
Charge transfer; Clouds; Interferometers; Lightning; Cloud-to-ground lightning flash; Electric field change; Fast breakdown; Frequency source; High-frequency pulse; Initial breakdown pulse; Initial electric field change; Interferometer narrow bipolar event; Narrow bipolar events; Very high frequency; Antennas; altitude; cloud to ground lightning; electric field; interferometer